Study on the Carbon Footprint of Schools in Pokhara, Nepal - Adhikari , Sandesh; Pokhrel, Rajib (Himalayan Journal of Applied Science and Engineering, 2025)
Academic institutions are significant contributors to carbon emissions due to large student populations, high energy use, waste generation, and extensive transportation demands. This study estimated the Carbon Footprint (CF) of eight public and private schools in Pokhara Metropolitan City (PMC) using the GHG Protocol across three scopes: (1) emissions from school buses and fuels, (2) electricity consumption, and (3) emissions from staff and student vehicles, waste, canteen fuels, textbooks, and paper. Schools with over 1,000 students were sampled through purposive and random sampling, ensuring representation of both public and private institutions. Data were collected using questionnaires, interviews, and school records, while students’ bag weights were measured to calculate Scope 3 emissions from textbooks and copies. Emissions were calculated as Metric Tons of CO2 equivalent (MTCO2e) using activity data and Emission Factors. The total CF was 409.76 MTCO2e/year, averaging 51.22 MTCO2e/year (76.25 for private schools, 26.19 for public). Scope 1, Scope 2, and Scope 3 emissions contributed 227.86, 5.1, and 176.8 MTCO2e, respectively. The per capita CF ranged from 0.011 to 0.055 MTCO2e/year, averaging 0.029 MTCO2e/year. This study offers critical insights into reducing GHG emissions, promoting sustainable development, and creating carbon-neutral academic institutions.